2017
DOI: 10.1002/adma.201702181
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent, Stretchable, and Self‐Healing Ionic‐Skin Triboelectric Nanogenerators for Energy Harvesting and Touch Applications

Abstract: Recently developed triboelectric nanogenerators (TENGs) act as a promising power source for self-powered electronic devices. However, the majority of TENGs are fabricated using metallic electrodes and cannot achieve high stretchability and transparency, simultaneously. Here, slime-based ionic conductors are used as transparent current-collecting layers of TENG, thus significantly enhancing their energy generation, stretchability, transparency, and instilling self-healing characteristics. This is the first demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
268
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 343 publications
(272 citation statements)
references
References 49 publications
4
268
0
Order By: Relevance
“…Functional materials are susceptible to breakdown due to the mechanical deformation–induced or accidental damage, resulting in the loss of structure and functionality which affects seriously the durability and lifetime of device. To address the key challenge, several self‐healing materials have been developed that can restore autonomously their structures and functions after mechanical damage . Disulfide bond, as a kind of dynamic covalent bond based on thiol/disulfide dynamic exchange reactions, can accomplish efficiently the self‐healing process in polymer through various external stimuli such as heat, light, and pH .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional materials are susceptible to breakdown due to the mechanical deformation–induced or accidental damage, resulting in the loss of structure and functionality which affects seriously the durability and lifetime of device. To address the key challenge, several self‐healing materials have been developed that can restore autonomously their structures and functions after mechanical damage . Disulfide bond, as a kind of dynamic covalent bond based on thiol/disulfide dynamic exchange reactions, can accomplish efficiently the self‐healing process in polymer through various external stimuli such as heat, light, and pH .…”
Section: Introductionmentioning
confidence: 99%
“…To address the key challenge, several selfhealing materials have been developed that can restore autonomously their structures and functions after mechanical damage. [18][19][20][21][22] Disulfide bond, as a kind of dynamic covalent bond based on thiol/disulfide dynamic exchange reactions, can accomplish efficiently the self-healing process in polymer through various external stimuli such as heat, [23] light, [24] and pH. [25] Moreover, the mild healing condition [26] and high healing efficiency [27] of self-healing polymer based on disulfide bond make it an ideal candidate for healed wearable applications.…”
Section: Introductionmentioning
confidence: 99%
“…[44] We demonstrated a TENG, with PVA slime as the STIC and silicone rubber as an active triboelectic layer (Figure 18a). The PVA slime (100% transmittance for visible light) is a borate ion cross-linked PVA hydrogel, formed by weak hydrogen bonding between the OH group of PVA and borate ions.…”
Section: Triboelectric Nanogeneratorsmentioning
confidence: 99%
“…Our group demonstrated that PVA slime formed by the weak hydrogen bonding between the OH groups of PVA and the tetrafunctional borate ions produces a self-healing effect. [44] The bonds are in a state of dynamic equilibrium, which can be easily broken and formed without any external stimuli. Zhi and co-workers also reported a self-healing PAA hydrogel using vinyl hybrid silica nanoparticles and hydrogen bonding.…”
Section: Challenges and Outlookmentioning
confidence: 99%
See 1 more Smart Citation